Powerful sources of pulse high-frequency electromechanical transducers for measurement, testing and diagnostics - Plesnetsov, S.Yu.; Petrishchev, O.N.; Mygushchenko, R.P.; Suchkov, G.M.; Sotnik, S.V.; Kropachek, O.Yu. (Електротехніка і електромеханіка, 2018)
Aim. Development of powerful current radio pulses generators (CRPG) for powering high-frequency electromechanical transducers based on IGBT transistors. Methodology. To carry out the research, the statements of the magnetic and electromagnetic fields interaction with electric and ferromagnetic material, electric circuits, structure of radio electronic devices theory were used. Results. The main provisions for creating powerful broadband generators for powering electromechanical transducers based on IGBT transistors are determined. It is shown that the generators intended for use in measurements, testing and diagnostics should provide adjustment of the frequency and duration of the output current pulses, and also provide current in the transducer inductor of several hundred amperes. The connection between the power frequency of the resonant electromechanical transducer and the gap between the transducer and the surface of the metal being diagnosed is established. A CRPG variant for powering electromechanical transducers in the frequency range 1 ... 3 MHz and the duration of current pulses of 1 ... 20 periods of the filling frequency is developed and manufactured. The peak current in the inductor of a high-frequency electromechanical transducer has reached 450 A. Novelty. For the first time, the possibility of using powerful IGBT transistors in electronic devices working in a key mode in push-pull circuits for feeding high-frequency electromechanical transducers is shown. Practical value. Using the results obtained will allow the creation of new instruments for measurement, control and diagnostics with wider characteristics.